Asuhan Akupuntur pada Kasus Sulit Buang Air Besar di Praktik Mandiri Sely Meting Pluit Jakarta Utara - Sely Meting; Amal Prihatono; Mayang Wulandari; Chantika Mahadini (Lembaga Pengembangan Kinerja Dosen, 2026)
Constipation is a global health problem experienced by about 14% of the adult population and 30% of the elderly. Around 23% occurs in women and 11% in men in Asia, including Indonesia. The aim of the study was to provide acupuncture care for constipation cases at Sely Meting Independent Practice, Pluit, North Jakarta. The research method used was a case study, with a sample of 1 person using purposive sampling, and data collection was carried out using a client data sheet instrument (DSI). The acupuncture points used in the therapy were LI4, KI6, LI11, SP15, BL25, ST25, ST44. The therapy was provided in 12 sessions, twice a week for 6 weeks. The analysis of the case study results used content analysis. Research using the case study method found a significant difference between the first therapy session and the twelfth therapy session. Patient complaints in the final session improved from difficulty in bowel movements to normal. Acupuncture therapy at this point can be recommended to therapists in managing patients based on syndromes and a high-fibre diet therapy.